Grapevines mycorrhizal colonization under organic and conventional production systems in Santa Catarina State - Bettoni, Jean Carlos (2022)
Microbiological indicators are used to assess soil quality and to compare management forms in agricultural production systems. The objective of this study was to evaluate the grapevines mycorrhizal colonization in production systems under organic and conventional management in Tangará and Videira counties, Santa Catarina State. Mycorrhizal colonization rates and arbuscular mycorrhizal fungi spores density in soil were evaluated. In the organic systems, compared to conventional systems, increases in mycorrhizal colonization rate and density of arbuscular mycorrhizal fungi spores in soil were observed. The results suggest that variables associated with mycorrhizal colonization can be used as microbiological indicators for assessing soil quality in vineyards.